2019
DOI: 10.1016/j.jshs.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic alterations after two high-intensity intermittent training protocols in endurance runners

Abstract: PurposeThis study aimed to evaluate running kinematic characteristics during the early and late stages of 2 high-intensity intermittent training (HIIT) protocols with similar external load but different average running pace, as well as to compare the fatigue-induced changes during both HIIT protocols at a kinematic level.MethodsEighteen endurance runners were tested on a track on 2 occasions: 10 runs of 400 m with 90–120 s recovery between running bouts (10 × 400 m), and 40 runs of 100 m with 25–30 s recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…In general, running mechanics pattern remained largely unaffected between early and late stages (i.e., from first to last interval) of our proposed HIIE, a finding also reported elsewhere. 4,22,23 For instance, intense interval training session consisting of either 10 runs of 400 m (rest = 60-180 s) or 40 runs of 100 m (rest = 25-30 s) did not modify the running kinematics of well-trained male runners. 4,23 However, having individuals constrained to run at a set velocity during fatigued running lacks ecological validity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In general, running mechanics pattern remained largely unaffected between early and late stages (i.e., from first to last interval) of our proposed HIIE, a finding also reported elsewhere. 4,22,23 For instance, intense interval training session consisting of either 10 runs of 400 m (rest = 60-180 s) or 40 runs of 100 m (rest = 25-30 s) did not modify the running kinematics of well-trained male runners. 4,23 However, having individuals constrained to run at a set velocity during fatigued running lacks ecological validity.…”
Section: Discussionmentioning
confidence: 94%
“…4,22,23 For instance, intense interval training session consisting of either 10 runs of 400 m (rest = 60-180 s) or 40 runs of 100 m (rest = 25-30 s) did not modify the running kinematics of well-trained male runners. 4,23 However, having individuals constrained to run at a set velocity during fatigued running lacks ecological validity. 10 Our spring-mass model results are partially in accordance with previous observation of modified mechanical behaviour towards lower vertical stiffness but constant leg stiffness during intervaltraining treadmill runs.…”
Section: Discussionmentioning
confidence: 94%
“…Only 2 studies 10,18 reported adequately the inclusion and exclusion criteria used. One study 6 did not use adequate statistical analysis and 6 studies 4,6,12,13,19,29 omitted information on inclusion and exclusion criteria.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…Despite the methodological rigor of our systematic review, we recognize several limitations of this study. First, 62.5% of the studies included in this systematic review 6,12,13,18,19 reported the psychometric properties of the 2D video analysis as a secondary objective. Therefore, relevant discussions on the psychometric properties of the 2D video analysis were not provided.…”
Section: Limitationsmentioning
confidence: 99%
“…About five million years ago, humans further evolved and developed complex foot morphological characteristics (e.g., heel, arch, and enlarged first metatarsal bone) to adapt to the needs of various activities, such as upright standing, walking, and endurance running [1]. As the direct complex contact area between the lower extremities and the ground/interface, the human foot plays an important role in supporting body mass in both static and dynamic upright locomotion [2,3] and is controlled by intrinsic and extrinsic foot muscles [4]. On account of the complexity of the foot structure, morphological parameters (e.g., foot length, foot width, foot arch height) have been utilized to simplify the anatomical complexities of the foot and describe foot type in the clinical field [5,6].…”
Section: Introductionmentioning
confidence: 99%